2014
DOI: 10.4238/2014.july.25.26
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks and genetic diversity of Francisella noatunensis subsp orientalis isolated from farm-raised Nile tilapia (Oreochromis niloticus) in Brazil

Abstract: ABSTRACT. Francisella noatunensis subsp orientalis (FNO) is an emerging pathogen of warm water tilapia in a number of different countries. The disease caused by this bacterium in fish is characterized by a systemic granulomatous infection that causes high mortality rates during outbreaks. FNO has been previously described in Asia, Europe, and Central and North America. Its occurrence in South America has never been described. Since 2012, outbreaks of a granulomatous disease have been recorded in cage farms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 21 publications
5
52
1
1
Order By: Relevance
“…Since 2012, piscine francisellosis has been associated with high mortality in Southeast and South regions of Brazilian tilapia aquaculture farms, particularly during the winter (Leal, Tavares & Figueiredo ; Assis et al . ; Jatobá, Klipp & Hoppe ).…”
Section: Average Threshold Cycle (Ct) Range and Quantification Mean mentioning
confidence: 99%
“…Since 2012, piscine francisellosis has been associated with high mortality in Southeast and South regions of Brazilian tilapia aquaculture farms, particularly during the winter (Leal, Tavares & Figueiredo ; Assis et al . ; Jatobá, Klipp & Hoppe ).…”
Section: Average Threshold Cycle (Ct) Range and Quantification Mean mentioning
confidence: 99%
“…Previously, some important pathogens devastating tilapia within intensively produced systems were reported, such as Streptococcus agalactiae (Olivares-Fuster et al, 2008;Kayansamruaj et al, 2014a;Kayansamruaj et al, 2014b), Flavobacterium columnare (Figueiredo et al 2005; press-a,b), Francisella sp. (Soto et al, 2009;Jeffery et al, 2010;Leal et al, 2014), Edwardsiella spp. (Iregui et al, 2012;Soto et al, 2012), Aeromonas spp.…”
Section: Introductionmentioning
confidence: 97%
“…Previous work has shown that for tilapia mortality rates can be 100% in less than 48 to 72 h (Soto et al 2009a), 86.7 ± 23% in 5 d p.i. (Nguyen et al 2016), or 90% between 20 h and 8 d (Leal et al 2014). In our study, mortality did not correlate with the infection dose.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the disease follows a chronic progression characterized by the formation of multifocal white nodules in the spleen and other organs (Soto et al 2009a(Soto et al , 2012a. Mortalities can be high (Chen et al 1994, Leal et al 2014.…”
Section: Introductionmentioning
confidence: 99%